Assessing pediatric tobacco exposure using parent report: comparison with hair nicotine. (November 2018) - Groner, Judith; Rule, Ana; McGrath-Morrow, Sharon; Collaco, Joseph; Moss, Angela; Tanski, Susanne; McMillen, Robert; Whitmore, Regina; Klein, Jonathan; Winickoff, Jonathan; Wilson, Karen
Abstract Introduction The purpose of this study was to examine the relationships between screening questions for secondhand smoke (SHS) exposure and biomarker results using hair nicotine levels. Our ultimate goal was to develop sensitive and valid screening tools in pediatric clinical settings for SHS exposure. Methods Investigators developed a core set of questions regarding exposure. Data from two separate ongoing studies of well children and those with bronchopulmonary dysplasia (BPD) were used to assess the concordance between responses and hair nicotine levels. Sensitivity, a positive predictive value, and accuracy were examined. Results There was no single question with similar sensitivity in both populations. The question with the highest positive predictive value (90.8% well-cohort and 84.6% BPD cohort) for both the groups was whether the child had been exposed to in-home smoking in the last 7 days. The question with the highest accuracy for both groups was the number of smokers at home (0 vs ≥ 1), with an accuracy of 72.4% for well children and 79.0% for the BPD cohort. Conclusions There was a wide variability in the performance of specific questions. These data demonstrate that a "one-size-fits-all" approach to screening for secondhand tobacco smoke exposure may not be appropriate for all pediatric populations.